Bus stop location under different levels of network congestion and elastic demand - Alonso, Borja; Moura, José Luis; dell’Olio, Luigi; Ibeas, Ángel (Transport, 2011)
The article analyses optimal bus stop locations under different network congestion levels applying a bi-level optimisation model, covering an upper level minimizing an overall cost function (Social Cost) and a lower level that includes a modal split assignment model. This model is applied to Santander city (Spain) under a range of demand levels, starting from very low to high congestion, representing the evolution of variables in each case and analysing different solutions. The optimal distances between stops obtained for each demand and congestion level indicate that very low demands produce wider spaces. However, as demand increases, accessibility to public transport service should be increased and then spacing between bus stops drops to 360 metres. First Published Online: 07 Jul 2011